Compassion Fatigue and Adopted Coping Strategies of Mental Health Service Providers Working in A Regional Psychiatric Hospital in Nigeria - Joyce Omoaregba; Oladotun Adeyemo; Afolabi Aroyewun; Blessing Uteh (Journal of Behavior Therapy And Mental Health, 2016)
Background: Mental health service providers sometimes suffer burden resulting from their care of mentally ill individuals, and this burden could be modulated by the coping mechanisms they adopt. Objective: This study aimed to investigate the relationships between gender, coping strategy and compassion fatigue of mental health service providers in a mental health facility in Nigeria Method: This was a cross-sectional study which recruited 234 mental health service providers working in a mental health facility in Nigeria, and they completed questionnaires (the Coping Strategy Inventory modified by Addison, Campbell-Jenkins & Sarpong and the Compassion Fatigue subscale of the Professional Quality of Life developed by Stamms. Results: Majority of the mental health service providers surveyed were at risk of compassion fatigue (75.2%), gender did not significantly impact on compassion fatigue (t =-0.111; p>0.05), and coping strategies jointly predicted compassion fatigue (F = 11.927; p<0.05; r=0.417). However, when analyzed separately, only the subgroup of emotional focused engagement coping and emotional focused disengagement coping strategies independently predicted compassion fatigue, (β =0.246, t= 3.3.511, p<0.05) and (β =0.226, t= 3.698, p<0.05) respectively. Conclusion: Mental health service providers have high risk of compassion fatigue and the emotional based coping strategies are associated with this. Measures are suggested to mitigate compassion fatigue among this professionals, to reduce the effect on them and their patients.
Keywords: Compassion fatigue